Evaluation of plasticity during deformation of carbon steel - V. Р. Fetisov (Литьë и металлургия, 2019)
The indicator of the degree of relative reduction of the cross-sectional area and the indicator of the degree of development of the necking, more sensitive to changes in the structural parameters and the deformation temperature of carbon steel compared to the traditional were proposed in comparison with the relative contraction and the true deformation index. The role of relaxation of internal stresses and increased mobility of dislocations in the formation of plastic properties of carbon steel is considered.